The Role of Digital Platforms in Scaling and Internationalizing Entrepreneurial Ventures - Kumar, Akul (My University, 2026)
Digital platforms have affected the way entrepreneurs develop and grow their businesses by providing them with the means to expand into global markets. The purpose of this investigation is to explore how platforms affect entrepreneurs and their ability to expand and sell internationally by providing an overview of how entrepreneurs use and interact with platform technology in their daily business operations. This research employs both qualitative and quantitative methods via survey data, illustrative case examples, and established theory to offer a better understanding of the effects of platform based growth on entrepreneurial development. The analysis has identified five main factors that enable entrepreneurs to grow their business using digital platforms; Automated and technological infrastructure, marketing tools for discoverability and tracking performance, learning and capability development, establishing trust and fairness, and providing direct services to entrepreneurs. These factors indicate that digital platforms provide entrepreneurs with an overall digital infrastructure vs solely being transactional marketplaces that provide entrepreneurs the ability to improve their operational efficiency, access global customers, and better manage the complexity of operating their business with minimal added human and financial resources. In this research, we have used the dynamic capabilities theory, Born global theory, and Platform ecosystem theory to understand the findings from the empirical research. It is clear from the findings that platform tools can have a positive impact on the growth of new businesses; however, for entrepreneurs to successfully scale their business, they must strategically combine their platform-based toolset, continuously develop digital capabilities, and manage their reliance on the governance structure of the platforms. Detailed analyses reveal aspects of trust, the opaque nature of algorithms, and responsiveness to requests to be central moderators of platform-based businesses' engagement with and resilience on the platforms over time. In addition to providing a holistic, experiential view on how professionals use digital platforms, this dissertation addresses both digital entrepreneurship and global commerce; concluding that scaling through platforms is an ongoing process of creating value based upon technology (affordance) combined with actions taken by entrepreneurs (agency). These conclusions will serve as a basis for further exploration into governance of platforms, development of digital capabilities and sustained success in entrepreneurial ecosystems.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business